KNOWLEDGE SHARING AND ITS IMPORTANCE FOR UNIVERSITIES’ COMMUNICATION PRACTICES - Lhadj Ahmed Karima, (International Journal of Innovative Technologies in Social Science, 2025)
This article examines how knowledge sharing underpins effective communicative practices in university institutions. Drawing on resource-based and stakeholder perspectives, it distinguishes tacit and explicit knowledge and outlines SECI dynamics to show how universities can convert individual know-how into organisational capability. The study identifies cultural, organisational, and technological enablers and barriers, emphasising the centrality of trust, cooperation, and performance systems, alongside digital tools such as LMS platforms and professional social networks. It argues that the strategic alignment of internal and external communication, along with tailored channels for diverse audiences, enhances reputation, innovation, and crisis readiness. The article concludes that cultivating a cooperative organisational culture and deploying well-designed mechanisms for knowledge circulation are strategic necessities for universities seeking quality, excellence, and sustainable development.